Rancang Bangun Robot 4WD Kendali Jarak Jauh Berbasis Arduino Uno dan RF24L01+PA/LNA - Br Pinem, Tessy Ocharina; Setyawan, Gogor Christmass; Budiati, Haeni (TIN: Terapan Informatika Nusantara, 2026)
Remote-controlled robots often face challenges related to communication stability and limited signal range. This study aims to design and develop a 4WD (Four Wheel Drive) robot based on Arduino Uno using NRF24L01+PA/LNA wireless communication and to evaluate system performance in terms of control responsiveness and communication reliability. The research method includes system design, hardware and software implementation, and performance testing under various distance conditions. The evaluated parameters include response time, data transmission success rate, and maximum communication range. The results show that the system achieves a communication success rate of 100% at 1 meter, 99% at 10 meters, and 96% at 50 meters. At the maximum distance of 200 meters, the system maintains a success rate of 75%. The response time is relatively low, enabling real-time control performance. This study contributes to the evaluation of NRF24L01 wireless communication performance in a 4WD robot system for remote control applications.